Effects of Physical Exercise on Cognitive Functioning and Wellbeing: Biological and Psychological Benefits - Mandolesi, Laura; Polverino, Arianna; Montuori, Simone; Foti, Francesca; Ferraioli, Giampaolo; Sorrentino, Pierpaolo; Sorrentino, Giuseppe (Frontiers in Psychology, 2018)
Much evidence shows that physical exercise (PE) is a strong gene modulator that induces structural and functional changes in the brain, determining enormous benefit on both cognitive functioning and wellbeing. PE is also a protective factor for neurodegeneration. However, it is unclear if such protection is granted through modifications to the biological mechanisms underlying neurodegeneration or through better compensation against attacks. This concise review addresses the biological and psychological positive effects of PE describing the results obtained on brain plasticity and epigenetic mechanisms in animal and human studies, in order to clarify how to maximize the positive effects of PE while avoiding negative consequences, as in the case of exercise addiction.